First report of marine luminescent bacteria and dinoflagellates from Isla del Coco National Park, Costa Rica. - Rojas-Alfaro, Rebeca; Umaña-Castro, Rodolfo; Rojas-Campos, Norman; Vargas-Montero, Maribel (Revista de Biología Tropical, 2020)
Introduction: Bioluminescence is the ability of certain organisms to transform chemical energy into light energy through various biochemical processes. Objective: Isolation and identification for the first time of luminescent bacteria of superficial marine water, and the identification of marine luminescent dinoflagellates of Isla del Coco National Park, Costa Rica. Methods: Samples of seawater obtained by diving at 20 m and at a surface level of 13 sites were collected. On the other hand, phytoplankton samples collected from the surface up to 30 m deep were analyzed in the surroundings of 8 sites of Cocos Island, and several luminescent species belonging to the genera Ornithocercus and Ceratocorys were determined. Results: Seven luminescent bacterial isolates were obtained, they were identified and characterized biochemically by means of an automated platform (Vitek) with high levels of confidence, they were taxonomically located within the genus Vibrio, 2 species: V. alginolyticus and V. parahaemolyticus, in addition, some isolates presented resistance to the antibiotic ampicillin and 100% hemolytic capacity. This research shows evidence of the presence of marine microscopic species in Cocos Island, Costa Rica, capable of presenting the phenomenon of luminescence, so that further study would be relevant in terms of the importance of these microorganisms in the production of metabolites secondary and as indicators of harmful algal blooms, so it is necessary to conduct more scientific research to determine their biotechnological potential. Conclusions: In the same way, the results obtained in this investigation suggest expanding the collection and isolation of luminescent microorganisms, accompanied by a biochemical and molecular characterization, in order to explore the microbial diversity associated with luminescence events and determine the environments in which that these species develop.